A Review: Enhanced Anodes of Li/Na-Ion Batteries Based on Yolk–Shell Structured Nanomaterials - Wu, Cuo; Tong, Xin; Ai, Yuanfei; Liu, De-Sheng; Yu, Peng; Wu, Jiang; Wang, Zhiming M. (Nano-Micro Letters, 2018)
Lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) have received much attention in energy storage system. In particular, among the great efforts on enhancing the performance of LIBs and SIBs, yolk–shell (YS) structured materials have emerged as a promising strategy toward improving lithium and sodium storage. YS structures possess unique interior void space, large surface area and short diffusion distance, which can solve the problems of volume expansion and aggregation of anode materials, thus enhancing the performance of LIBs and SIBs. In this review, we present a brief overview of recent advances in the novel YS structures of spheres, polyhedrons and rods with controllable morphology and compositions. Enhanced electrochemical performance of LIBs and SIBs based on these novel YS structured anode materials was discussed in detail. Highlights: 1 In this review article, we have emphasized the recent developments of YS structured anodes and their applications for enhanced electrochemical performance in LIBs and SIBs. 2 An overview of recent advances in the novel YS structures of spheres, polyhedron and rods with controllable shape and compositions is provided. 3 Enhanced electrochemical performance of LIBs and SIBs based on these novel YS structured anode materials is discussed in detail.